The radiative association of PO/PH+ and the photodissociation of PH+ - Chen, Yang; Lin, Xiaohe; Xiao, Lidan; Li, Zijian; Zhang, Songbin; Cheng, Yongjun; Wu, Yong; Yan, Bing (Frontiers in Astronomy and Space Sciences, 2024)
The potential energy curves (PECs) and transition dipole moments (TDMs) of PH+ and PO are computed with the multireference configuration interaction method, and the cross-sections for the radiative association (RA) of PH+ and PO, which is the most efficient way to form the ground states, are presented via the quantum mechanical (QM) theory and computed using ab initio molecular data. The thermal rate coefficients are also expressed and fitted with the standard formula kT=AT300αe−βT in the range of 10 K–15,000 K. Meanwhile, the photodissociation, that is the inverse process of RA for PH+, is also studied, including eight photodissociation channels for the computation of state-resolved cross-sections. Careful comparisons with the Leiden Observatory database are made. Considering the cross-sections mentioned above, the local thermodynamic equilibrium cross-sections at the temperatures of 0, 500, 1,000, and 2,000 K are also shown. We expect the results to be helpful for studies of phosphorus chemistry in the interstellar medium and planetary atmospheres.